Pemanfaatan Belimbing Wuluh (Averrhoa Bilimbi) dalam Pembuatan Sabun Cuci Piring dan Asam Sunti yang Bernilai Ekonomis - Maisarah; Fitra Azkia Ramadhani; Nuryani Kasman; Chusnur Rahmi (LSM Catimore dan Sahabat, 2023)
Dish soap is generally very used in everyday life, especially housewives. One of the natural ingredients that can be used in the manufacture of dish soap is Belimbing Wuluh. Belimbing Wuluh (Averrhoa Bilimbi) extract contains flavonoids, saponins and alkaloids, tannins, glucosides, sulfur, oxalic acid, phenol, volatile oil, pectin, calcium oxalate, formic acid, peroxidase and phenol. The content of the extract in starfruit contains triterponoid and flovanoid compound groups consisting of the presence of O-H, C=O, C=C, C-H, and C-OH groups. Belimbing Wuluh extract contains flovanoid which acts as an antioxidant and antibacterial. Therefore, in this study, dish soap was made from belimbing wuluh extract. In this study, researchers made 2 (two) products at once, in which belimbing wuluh extract was used as dishwashing soap, and residue from belimbing wuluh was used as a cooking spice (sunti acid). Sunti acid is a kind of pickle or cooking spice which is dried until it becomes brownish in color, and given salt, this salting process aims to draw water out in the starfruit tissue so that sunti acid can last longer. Sunti acid is used as a cooking ingredient, especially for Aceh cuisine, which is the hallmark of the cuisine of the Acehnese peopleDish soap is generally very used in everyday life, especially housewives. One of the natural ingredients that can be used in the manufacture of dish soap is Belimbing Wuluh. Belimbing Wuluh (Averrhoa Bilimbi) extract contains flavonoids, saponins and alkaloids, tannins, glucosides, sulfur, oxalic acid, phenol, volatile oil, pectin, calcium oxalate, formic acid, peroxidase and phenol. The content of the extract in starfruit contains triterponoid and flovanoid compound groups consisting of the presence of O-H, C=O, C=C, C-H, and C-OH groups. Belimbing Wuluh extract contains flovanoid which acts as an antioxidant and antibacterial. Therefore, in this study, dish soap was made from belimbing wuluh extract. In this study, researchers made 2 (two) products at once, in which belimbing wuluh extract was used as dishwashing soap, and residue from belimbing wuluh was used as a cooking spice (sunti acid). Sunti acid is a kind of pickle or cooking spice which is dried until it becomes brownish in color, and given salt, this salting process aims to draw water out in the starfruit tissue so that sunti acid can last longer. Sunti acid is used as a cooking ingredient, especially for Aceh cuisine, which is the hallmark of the cuisine of the Acehnese people